2023
DOI: 10.24815/siele.v10i1.25401
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering EFL learners’ demotivation towards English online learning during the Covid-19 pandemic in Indonesia

Abstract: Online learning during the Covid-19 pandemic has demotivated Indonesian tertiary EFL students to learn English, which affected their English performance and achievement. This article ferrets out the features of the EFL students’ demotivation, the factors affecting their demotivation, the solution to reduce their demotivation, and the implication of their demotivation towards their English performances and achievement. The data for this descriptive quantitative research were collected through an online open-end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…A subsequent survey conducted by this study after the peak of the COVID-19 pandemic, when students had returned to university, did not show any significant instances of demotivation among the participants. The two different findings of Iftanti et al (2023) and this study on EFL students' amotivation in two different time settings can indicate successful adaptation to online learning.…”
Section: Students' Motivation and Autonomous Learnersmentioning
confidence: 62%
See 4 more Smart Citations
“…A subsequent survey conducted by this study after the peak of the COVID-19 pandemic, when students had returned to university, did not show any significant instances of demotivation among the participants. The two different findings of Iftanti et al (2023) and this study on EFL students' amotivation in two different time settings can indicate successful adaptation to online learning.…”
Section: Students' Motivation and Autonomous Learnersmentioning
confidence: 62%
“…Iftanti et al, 2023, p. 104). While Iftanti et al (2023) found demotivation students at the university level, Nuzulia and Kepirianto (2020, p. 272) showed similar experiences among Junior high school (SMP) students who were passive and afraid of speaking English. The successful adaptation was indicated by the increased motivation of students to attend online learning when the survey was conducted after the students returned to offline classes.…”
Section: Students' Motivation and Autonomous Learnersmentioning
confidence: 95%
See 3 more Smart Citations